Less Social Support for Patients With COVID-19: Comparison With the Experience of Nurses - Li, Zhenyu; Ge, Jingwu; Feng, Jianping; Jiang, Riyue; Zhou, Qin; Xu, Xiaolin; Pan, Yinbing; Liu, Shijiang; Gui, Bo; Wang, Zhongyun; Zhu, Bin; Hu, Yimin; et al. (Frontiers in Psychiatry, 2021)
Context. Since December 2019, more than 80,000 patients have been diagnosed with coronavirus disease 2019 (COVID-19) in China. Social support status of COVID-19 patients, especially the impact of social support on their psychological status and quality of life, needs to be addressed with increasing concern. Objectives. In this study, we used social support rating scale (SSRS) to investigate the social support in COVID-19 patients and nurses. Methods. The present study included 186 COVID-19 patients at a Wuhan mobile cabin hospital and 234 nurses at a Wuhan COVID-19 control center. Responses to a mobile phone app-based questionnaire about social support, anxiety, depression, and quality of life were recorded and evaluated. Results. COVID-19 patients scored significantly lower than nurses did on the Social Support Rating Scale (SSRS). Among these patients, 33.9% had anxiety symptoms, while 23.7% had depression symptoms. Overall SSRS, subjective social support scores and objective support scores of patients with anxiety were lower than those of patients without anxiety. This result was also found in depression. In addition, all dimensions of social support were positively correlated with quality of life. Interestingly, in all dimensions of social support, subjective support was found to be an independent predictive factor for anxiety, depression, and quality of life, whereas objective support was a predictive factor for quality of life, but not for anxiety and depression via regression analysis. Conclusion. Medical staffs should pay attention to the subjective feelings of patients and make COVID-19 patients feel respected, supported, and understood from the perspective of subjective support, which may greatly benefit patients, alleviate their anxiety and depression, and improve their quality of life.